ACC and vaterite as metastable intermediates in the solution based crystallization of CaCO3 - Rodriguez-Blanco, Juan (Springer International Publishing, 2017)
Amorphous calcium carbonate (ACC) and vaterite are not very common in abiotic systems, but they play a very significant role in biomineralization processes and are key in the global carbon cycle. Despite their importance, many questions about the factors affecting the mechanisms of formation and stabilization during biomineralization processes remain unanswered, because most of the information so far is obtained from experimental synthesis in abiotic conditions. In recent years, it has been shown that ACC and vaterite have complex structures and chemistries. Their formation and stability are drastically affected by pH, the presence of (in)organics (e.g., Mg2+, SO42−, aspartic acid, glutamic acid, citric acid, etc.), temperature, and supersaturation. Changes in any of these variables affect the lifetime of ACC and the crystallization rates and pathways to vaterite or other CaCO3 polymorphs. In addition, the morphologies, composition, sizes, and properties of ACC and vaterite are highly affected. This chapter provides a perspective on the current state-of-the-art research on the formation and crystallization mechanisms of ACC to vaterite.
New Perspectives on Mineral Nucleation and Growth
Keywords: Amorphous calcium carbonate (ACC); Vaterite; Carbonates; Nucleation; Spherulitic growth; Biomineralization; Nanoscience & Materials; Smart & Sustainable Planet; CRYSTALLIZATION; MINERALOGY; Mineralogy and crystallography; NUCLEATION; carbonates